4 - Pratiques urbaines et imbroglio spatial : Brazzaville de la fin de la période coloniale au début du XIXe siècle - Yekoka Jean Félix (Africa Development, 2021)
A product of colonial will at the end of the nineteenth century, Brazzaville presents the image of an artificial city. Its spatial hypergrowth, which in no way results from a popular quest to optimize or satisfy a need for housing, reinforces its fragmentation. A macrocephalic city, Brazzaville’s urban fabric includes a range of activities (real estate, petty trade, small-scale agriculture, parking lots, car washing, market gardening, marking, evangelization campaigns, mobile telephone stands, etc.), which take the public space by storm. Within these practices, the dynamics between the different actors in- volved is conflictual as they engage in a mad race for public space, which leads to its alienation. The alienation of public space causes confusion in its administration. In response to the different issues and challenges facing the public authorities regarding the urban public space of Brazzaville, scenarios can be envisaged over the long term.